2003
DOI: 10.1111/j.1447-0578.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between steroids concentration in follicular fluid, pronuclear morphology and embryo qualities in in vitro fertilization

Abstract: Background: Several parameters of early embryo development are known as predictors of implantation success. Recently, zygote or embryo morphological assessments are thought to be a major method of selection in embryo transfer. We expected that the concentrations of the steroids in follicular fluid (FF) were associated with oocyte maturation and embryo quality. In the present paper, we evaluated the relationship of several parameters. Methods:We investigated 105 samples of FF from 22 subjects by in vitro fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been reported that progesterone/estradiol ratios were higher in the follicles of which oocytes were fertilized 1 and these higher progesterone values were associated with the oocyte's fertilization capacity by intracytoplasmic sperm injection (ICSI) 2 . In contrast, our previous study found that there was no difference in the FF steroid concentrations between the fertilized group and unfertilized group 3 …”
Section: Introductionmentioning
confidence: 66%
“…It has been reported that progesterone/estradiol ratios were higher in the follicles of which oocytes were fertilized 1 and these higher progesterone values were associated with the oocyte's fertilization capacity by intracytoplasmic sperm injection (ICSI) 2 . In contrast, our previous study found that there was no difference in the FF steroid concentrations between the fertilized group and unfertilized group 3 …”
Section: Introductionmentioning
confidence: 66%
“…To further assess whether E2 can promote biological activities in hGCs, we first ascertained that endogenous ERs were able to transactivate an estrogen reporter construct in these cells. For this purpose, cultured hGCs from follicles of 14 patients were transfected with an ERE-Luc or a control (pGL2) vector to measure their luciferase activity with 10 nM E2 treatment during 24 h. We chose this concentration to reproduce the intrafollicular concentration measured in follicular fluids of antral follicles [ 21 , 22 ]. In hGCs transfected with the ERE-Luc, pairwise comparison of vehicle (V, solvent) and E2-treated hGCs from each patient showed that E2 stimulated by 3.2-fold ( p < 0.001) the ERE-dependent luciferase activity ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The follicular fluid concentration of progesterone in mature COC was significantly higher than that in the immature stage [13]. It has been suggested that steroid concentrations in the follicular fluid are associated with oocyte maturation and embryo quality [14-16]. …”
Section: Discussionmentioning
confidence: 99%